ANALISIS HASIL BELAJAR SISWA KELAS V DENGAN METODE DARING DI MASA PANDEMI DI SDN 016 BERINGIN JAYA - Supriyatna, Eka Novia; Zufriady, Zufriady; Putra, Zetra Hainul (Tunjuk Ajar : Jurnal Penelitian Ilmu Pendidikan, 2025)
Online learning is distance learning using the internet network. Online learning is a new experience for teachers, students and parents. So the implementation is very different and this will be related to the learning outcomes of students in online learners. This study aims to find out the learning outcomes of students with online methods and describe the factors that affect them. This type of research is qualitatively descriptive. The study was conducted at SD Negeri 016 Beringin Jaya with the research subjects of two teachers, six students and five parents of V-grade students. The research technique is observation, interview and documentation with the research institute of interview guidelines so that researchers are more targeted. Data analysis techniques use the Miles &Huberman analysis model which consists of three stages namely data reduction, data display, withdrawal and verification of conclusions. The results of this study show that the implementation of online learning has not been effective, the learning outcomes of class V students have been well seen from the achievement of KKM and the factors that affect it, namely from students who include craft, discipline, ability and factors from outside the student, namely the limitations of the internet network, difficulties experienced by teachers and the role of parents.